An application of TPB constructs on energy-saving behavioural intention among university office building occupants: a pilot study in Malaysian tropical climate - Obaidellah, Unaizah Hanum; Danaee, Mahmoud; Mamun, M.A.A.; Hasanuzzaman, Md.; Rahim, Nasrudin Abd (Springer, 2019)
Buildings account for a vast amount of energy consumption in Malaysia. Occupant behaviour patterns are a major factor affecting the energy performance of buildings. Identifying energy waste due to occupant behaviour will allow stakeholders to develop effective strategies to curtail energy consumption in buildings. The purpose of this study was to investigate the effects of theory of planned behaviour constructs on energy-saving behavioural intention among university building occupants. Data from a survey questionnaire was collected from 292 occupants (students and staff) at one case study building at a public university in Malaysia. Data analysed using the structural equation model showed that attitude and perception significantly influence occupants’ energy-saving behaviour. Our results indicate that respondents showed moderate behaviour on three sub-constructs: duration of equipment use, frequency of equipment use, and energy saving practice. The current pilot study provides a basis for an improved theoretical framework that considers other variables to be applied in a larger scale study. The implications for behaviour models in terms of policy recommendations and suggestions for occupant engagement campaigns are discussed. © 2019, Springer Nature B.V.